A Review of Bee Captures in Pest Monitoring Traps and Future Directions for Research and Collaboration. Issue 1 (30th December 2021) - Spears, Lori R; Christman, Morgan E; Koch, Jonathan B U; Looney, Chris; Ramirez, Ricardo A
Abstract: Bees provide an important ecosystem service by contributing to the pollination of crop and wild plant species. Multiple bee species, however, are in decline due to factors such as habitat loss and fragmentation, inadequate food availability, improper management practices, climate change, and pressures from pathogens and pests, including exotic species. Concerns about pollinator declines and implications for ecosystem services have led to efforts to create and restore pollinator habitat, refine pest management practices, improve detection of pests and exotic species that threaten native bees, and monitor populations to identify and protect vulnerable bee species and communities. A variety of methods are used to monitor bee populations, some of which use visual stimuli that mimic natural cues used to locate floral resources. Bees also find their way into traps that use both visual and olfactory cues to attract pest insects. On one hand, researchers work to improve pest monitoring tools to increase target captures and reduce bee bycatch. On the other, analysis of bee bycatch can help assess biodiversity, determine population fluctuations and range expansions or contractions, support monitoring efforts, and identify patterns and processes of broader ecological interest. These different fields of research should not be seen as conflicting goals, but rather an opportunity for greater complementarity and collaboration. This article reviews the biological and ecological bases for bee attraction to traps, summarizes recent trends in bycatch research, highlights future research priorities, and identifies opportunities for collaborative data sharing to maximize existing resources.